Identification of six novel P450 oxidoreductase missense variants in Ashkenazi and Moroccan Jewish populations - Tomková, Mária; Marohnic, Christopher C; Gurwitz, David; Seda, Ondřej; Masters, Bettie Sue Siler; Martásek, Pavel (Pharmacogenomics, 2012)
BACKGROUND: The enzyme NADPH-P450 oxidoreductase (POR) is the main electron donor to all microsomal CYPs. The possible contribution of common POR variants to inter- and intra-individual variability in drug metabolism is of great pharmacogenetic interest. AIM: To search for POR polymorphic alleles and estimate their frequencies in a Jewish population. MATERIALS & METHODS: We analyzed the POR gene in 301 Ashkenazi and Moroccan Jews. RESULTS: A total of 30 POR SNPs were identified, nine in the noncoding regions and 21 in the protein-coding regions (ten synonymous, 11 missense). Six of these missense variants are previously undescribed (S102P, V164M, V191M, D344N, E398A and D648N). CONCLUSION: The data collected in this study on missense POR SNPs, interpreted in light of the crystallographic structure of human POR, indicate that some POR missense variants may be potential biomarkers for future POR pharmacogenetic screening.
Keywords: NADPH-Ferrihemoprotein Reductase; Israel; Female; Maroko; židé; ženské pohlaví; farmakogenetika; jednonukleotidový polymorfismus; Morocco; Gene Frequency; lidé; NADPH-cytochrom c-reduktasa; Polymorphism, Single Nucleotide; Mutation, Missense; Linkage Disequilibrium; vazebná nerovnováha; frekvence genu; Jews; Models, Molecular; Humans; Izrael; molekulární modely; missense mutace; Male; Haplotypes; Pharmacogenetics; Sequence Analysis, DNA; haplotypy; genetické markery; mužské pohlaví; sekvenční analýza DNA; Genetic Markers